DESIGN OF COMMUNAL WASTEWATER TREATMENT PLANT (CASE STUDY IN DEPOK VILLAGE, TRENGGALEK, EAST JAVA) - Ratih Arum Sari; Arqowi Pribadi; Dyah Ratri Nurmaningsih; Sulistiya Nengse; Yustrianti Yustrianti (Universitas Lambung Mangkurat, 2022)
Planning for a communal scale Wastewater Treatment Plant (WWTP) in Depok Village, Trenggalek Regency, East Java is needed because most of the wastewater in Depok Village is only treated with septic tanks. This study aims to plan a communal scale WWTP design based on the generation of domestic and non-domestic wastewater in Depok Village. The WWTP planning in this study was carried out based on the results of laboratory test parameters for pH, TSS, BOD, COD, total coliform, fatty oil, and ammonia. Based on the test results, it is known that the parameters exceed the required limits according to the Minister of Environment Regulation No. 68 of 2016 is the parameter of TSS, ammonia, and total coliform. The units that are planned are barscreen unit is planned to have a length of 8.65 m, a width of 2.65 m, and a depth of 3 m. The initial settling basin is planned to have a length of 11 m, a width of 3 m, and a depth of 4 m. The anaerobic biofilter unit is planned to have a length of 15 m, a width of 7.5 m, and a depth of 2.5 m. The aerobic biofilter unit is planned to have a length of 16.5 m, a width of 8.5 m, and a depth of 2 m. The final settling basin is planned to have a length of 37 m, a width of 18.5 m and a depth of 2.5 m. The control body is planned to have a length of 9.5 m, a width of 5 m and a depth of 2 m. Meanwhile, disinfection is planned using a disinfectant pump.